Diagnostic practices and disease surveillance in Canadian children with congenital central hypoventilation syndrome - Reshma Amin; Theo J Moraes; Amy Skitch; Meredith S Irwin; Stephen Meyn; Manisha Witmans (Canadian Respiratory Journal)
OBJECTIVE: To assess the diagnostic and surveillance practices of Canadian pediatric subspecialists for children with congenital central hypoventilation syndrome (CCHS).